Effect of Rock Particle Content on the Mechanical Behavior of a Soil-Rock Mixture (SRM) via Large-Scale Direct Shear Test - Longqi Liu; Xuesong Mao; Yajun Xiao; Qian Wu; Ke Tang; Feifei Liu (Advances in Civil Engineering)
The mechanical strength of the landslide deposits directly affects the safety and operation of the roads in the western mountainous area of China. Therefore, the research is aimed at studying the mechanisms of a landslide deposit sample with different rock particle contents by analyzing its characteristics of the stress-strain behavior, the “jumping” phenomenon, the volumetric strain, and the shear strength parameters via a large-scale direct shear test. Stress-strain results show that stress-strain curves can be divided into 3 different stages: liner elastic stage, yielding stage, and strain-hardening stage. The shear strength of SRM behaves more like “soil” at a lower rock particle content and behaves more like “rock joints” at a higher rock particle content. Characteristics of the “jumping” phenomenon results show that the “intense jumping” stage becomes obvious with the increasing rock particle content and the normal stress. However, the lower the rock particle content is, the more obvious the “jumping” phenomenon under the same normal stress is. Volumetric strain results show that the sample with a lower rock particle content showed a dilatancy behavior under the low normal stress and shrinkage behavior under the high normal stress. The dilatancy value becomes smaller with the increasing normal stress. The maximum shear stress value of the rock particle content corresponds to the maximum value of dilatancy or shrinkage. We also conclude that the intercept of the Mohr failure envelope of the soil-rock mixture should be called the “equivalent cohesion,” not simply called the “cohesion.” The higher the normal stress and rock particle content are, the bigger the equivalent cohesion and the internal friction angle is.